Multidimensional evaluation and strategic framework for integrated development of urban agglomerations in underdeveloped regions - Fang Wang; Xin Li (PLoS ONE, 2026)
As a complex spatial giant system leading regional development, studying the integration level and coupling drive of urban agglomerations is of great significance for the sustainable development of urban agglomeration systems. This study established an integrated evaluation index system for the Lanzhou-Xining urban agglomeration (LXUA) and analyzed the spatio-temporal evolution characteristics of multidimensional and comprehensive integration. In addition, based on the parameter optimal geographic detector model, the coupling driving mechanism of the interaction between variable factors on the comprehensive integration of urban agglomerations was revealed. Research has found that: (1) In terms of temporal changes, there are significant differences in the integration level of different dimensions in the LXUA. Among them, the integrated indices of economic development, public services, and urban space have relatively small fluctuations, while the integrated indices of ecological environment and infrastructure have relatively large fluctuations. The problem of insufficient and unbalanced regional economic development in the LXUA is particularly prominent. (2) In terms of spatial distribution, the spatial differentiation characteristics of the integration level of each dimension are obvious, with high-value areas mainly concentrated in core cities, while underdeveloped counties lag behind in development. The over-all integration level of the LXUA has been improved, but there is a prominent imbalance between dimensions and regions. It is necessary to strengthen cross regional cooperation and policy tilt to address the shortcomings of the economy and infrastructure, in order to achieve sustainable development. (3) The independent explanatory power of economic development and infrastructure factors on the comprehensive integration of urban agglomerations is strong through factor interaction detection. The interaction between infrastructure, public services, and urban spatial fac-tors has a nonlinear enhancement effect on the comprehensive integration of urban agglomerations. The research conclusion is helpful for formulating sustainable development strategies for urban agglomerations.